A Theoretical Study on the Efficacy and Mechanism of Combined YAP-1 and PARP-1 Inhibitors in the Treatment of Glioblastoma Multiforme Using Peruvian Maca Lepidium meyenii - Albert Gabriel Turpo-Peqqueña; Sebastian Luna-Prado; Renato Javier Valencia-Arce; Fabio Leonardo Del-Carpio-Carrazco; Badhin Gómez (Current Issues in Molecular Biology)
Glioblastoma multiforme (GBM) is one of the most aggressive and treatment-resistant forms of brain cancer. Current therapeutic strategies, including surgery, chemotherapy, and radiotherapy, often fail due to the tumor’s ability to develop resistance. The proteins YAP-1 (Yes-associated protein 1) and PARP-1 (Poly-(ADP-ribose)–polymerase-1) have been implicated in this resistance, playing crucial roles in cell proliferation and DNA repair mechanisms, respectively. This study explored the inhibitory potential of natural compounds from Lepidium meyenii (Peruvian Maca) on the YAP-1 and PARP-1 protein systems to develop novel therapeutic strategies for GBM. By molecular dynamics simulations, we identified N-(3-Methoxybenzyl)-(9Z,12Z,15Z)- octadecatrienamide (DK5) as the most promising natural inhibitor for PARP-1 and stearic acid (GK4) for YAP-1. Although synthetic inhibitors, such as Olaparib (ODK) for PARP-1 and Verteporfin (VER) for YAP-1, only VER was superior to the naturally occurring molecule and proved a promising alternative. In conclusion, natural compounds from Lepidium meyenii (Peruvian Maca) offer a potentially innovative approach to improve GBM treatment, complementing existing therapies with their inhibitory action on PARP-1 and YAP-1.